Upaya Pemerintah Kabupaten Badung dalam Meminimalisir Kasus Bunuh Diri - Kadek Agus Sudharma; Ida Bagus Anggapurana Pidada; Ida I Dewa Ayu Dwiyanti (Pusat Riset dan Inovasi Nasional, 2025)
Suicide is the act of taking one's own life by various means, either directly or gradually. The Badung Regency Government is working to prevent suicides, particularly at the Tukad Bangkung Bridge in Pelaga Village, by improving and securing the bridge area and installing CCTV. The Badung Regency Government is ready to assist, particularly by financing the construction of safety fences to prevent further suicide attempts. This research certainly uses the Empirical-juridical legal research method, which is a research method in which the legal research method is carried out by analyzing the law from the perspective of statutory regulations, and also observing how the law is implemented or applied in reality in society, an approach in legal research that aims to understand and analyze the law. Based on the results of the research that has been carried out. The efforts of the Badung Regency Government in Minimizing Suicide Cases, the qualifications for the act of ending one's own life or suicide in Article 345 of the Criminal Code state that